2014
DOI: 10.1016/j.chroma.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organothiophosphorus pesticides in water by liquid chromatography and post-column chemiluminescence with cerium(IV)

Abstract: A new, fast, selective and sensitive method has been developed for the simultaneous determination of nine organothiophosphorus (OTP) pesticides, namely omethoate, dimethoate, disulfoton-sulfoxide, methidathion, phosmet, malathion, diazinon, pirimiphos-methyl and chlorpyrifos. The pesticides were separated on a Kinetex C18 column by gradient elution with acetonitrile:water. A post-column basic hydrolysis of the pesticides and later a chemiluminescence (CL) reaction with cerium (IV) in acid medium was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…However, the method developed in this study provided satisfactory LODs using common equipment accessible in most analytical laboratories. Also, our LOD values for PIR and CLO were similar to the ones obtained by Catalá-Icardo et al [41], where a more sensitive detection (chemiluminiscence) was used.…”
Section: Comparison With Other Extraction Proceduressupporting
confidence: 87%
See 1 more Smart Citation
“…However, the method developed in this study provided satisfactory LODs using common equipment accessible in most analytical laboratories. Also, our LOD values for PIR and CLO were similar to the ones obtained by Catalá-Icardo et al [41], where a more sensitive detection (chemiluminiscence) was used.…”
Section: Comparison With Other Extraction Proceduressupporting
confidence: 87%
“…However, the LOD achieved for this pesticide was higher than other sample pretreatments (such as LDS-VSLLME [9], HS-SPME [13] or SPE combined with DLLME [6]). However, it should be mentioned that few studies have been reported for the simultaneous determination of the two [17,20] or three pesticides [41] investigated. Thus, the LODs assayed in this study were similar [20] or even better [17] than those described using magnetic functionalized materials in combination with highly sensitive and sophisticated techniques (GC-MS).…”
Section: Comparison With Other Extraction Proceduresmentioning
confidence: 99%
“…occasionally employed for other pesticides, like organothiophosphorus 20 , pyrethroids 21 or phenoxyacids. 22 The development of new LC-CL methods applied to other families of pesticides is very interesting due to the great advantages of these methods in terms of sensitivity, selectivity and simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Chemiluminescence accompanies the reaction of oxidation of phosphor-organic pesticides such as omethoate, dimethoate, disulphoton-sulphoxide, methidathion, phosmet, malathion, diazinon, pirimiphos-methyl and chlorpyrifos with cerium(IV) ions. The emitters are the excited products of pesticides oxidation whose emission increases in the presence of a surfactant -hexadecylpyridinium chloride monohydrate (HPC) [56]. This fact was employed for determination of these compounds in water samples, after their preliminary separation by HPLC .…”
Section: The Ce(iv)-analyte Reactions Systemsmentioning
confidence: 99%